Students as Health Promotion Influencers - Kurniawan, Firmanda Danang (BKM Public Health and Community Medicine, 2024)
Purpose: To explore the positive influence of influencers in health campaigns and the potential of students as influencers. Methods: The We Are Social report states that there were 139 million active social media users in Indonesia as of January 2024. In 2023, health-related content was the most frequently visited topic on social media, accounting for 36.96% of the audience's interest. Given the increasing number of social media users, these platforms can be positively utilized as educational tools to provide widespread health awareness. However, social media can also be a source of negative influence, such as the spread of misinformation. During the COVID-19 pandemic, approximately 4%-18% of people encountered and believed in misinformation about the virus over the past three years. Results: The government has addressed misinformation through legal measures, public education, and complaint platforms, but online misinformation continued to rise in 2022. One effective strategy to combat misinformation is engaging influencers in health promotion. Influencers, who wield influence through their attributes and reputations, can come from various backgrounds, including celebrities, politicians, healthcare professionals, and students. Collaborating with influencers can enhance credibility and engagement in health campaigns. Social media influencers can promote healthy behavior changes, positively impacting issues like smoking cessation, diet, and exercise. Students play a crucial role in health promotion interventions. Instagram, a widely used platform in 2024, is especially popular among 18-24-year-olds (the typical student age range). Influencers on Instagram are seen as credible, trustworthy, knowledgeable about the brands they support, and capable of building relationships with their audience. This presents an opportunity to involve students in health promotion through Instagram. Conclusion: Applying Minzberg’s Theory to manage influencer involvement in health organizations can be innovative. The organizational structure should include students as influencers (operating core), a Founder/CEO (strategic apex), managers (middle line), healthcare professionals or academics (technostructure), and support staff such as digital marketers, editors, and copywriters. This approach encourages active student participation in health promotion and allows them to apply classroom knowledge in real-world settings.